2019
DOI: 10.1002/nau.24041
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic syndrome and smoking are associated with persistence of nocturia after transurethral resection of the prostate

Abstract: Aims The aim of our study was to evaluate the relationship between smoking, metabolic syndrome (MetS) and persistence of nocturia in patients with moderate/severe nocturia (nocturia episodes ≥2), lower urinary tract symptoms (LUTSs), and benign prostatic enlargement (BPE) undergoing transurethral resection of the prostate (TURP). Methods From 2015 onward, a consecutive series of patients with moderate/severe nocturia (nocturia episodes ≥2), LUTS, and BPE undergoing TURP were prospectively enrolled. Medical his… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 36 publications
1
10
0
Order By: Relevance
“…In urology, very few studies have evaluated the role of curcuma to reduce inflammation with conflicting results and however none of the studies have evaluated the role of the highly bioavailable curcuma to improve symptoms after TURP [19,20]. In our study we confirm the role of Qurminin improving IPSS in a different population.…”
Section: Discussionsupporting
confidence: 72%
“…In urology, very few studies have evaluated the role of curcuma to reduce inflammation with conflicting results and however none of the studies have evaluated the role of the highly bioavailable curcuma to improve symptoms after TURP [19,20]. In our study we confirm the role of Qurminin improving IPSS in a different population.…”
Section: Discussionsupporting
confidence: 72%
“…Russo et al [10] showed that the presence of MetS worsened the symptoms of BPH, including PV. Additionally, De Nunzio et al [11] and Sebastianelli et al [33] underlined how MetS, with systemic inflammation, influence the response to the medical treatment of BPE.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, previous data have shown that patients with MetS could be refractory to medical treatments and may exhibit symptoms persistence after surgery [10,11]. In fact, MetS is associated with an increase in intravesical prostatic protrusion (IPP), together with an increase in prostate volume (PV), explaining the lack of satisfaction with medical therapy in those patients with metabolic alterations [10].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…98 Studies did not always collect data on comorbidities such as cardiovascular disease or T2D. 35 Patients with diabetes have been shown to have higher incidences of DO and patients also tend to be older, which is another factor that increases the likelihood of developing LUTS. 99,100 In addition, the following confounding factors could also lead to a variation in results.…”
Section: Discussionmentioning
confidence: 99%